2019
DOI: 10.3390/insects10110413
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis Reveals Immune Competence in Hemolymph of Bombyx mori Pupa Parasitized by Silkworm Maggot Exorista sorbillans

Abstract: The silkworm maggot, Exorista sorbillans, is a well-known larval endoparasitoid of the silkworm Bombyx mori that causes considerable damage to the silkworm cocoon crop. To gain insights into the response mechanism of the silkworm at the protein level, we applied a comparative proteomic approach to investigate proteomic differences in the hemolymph of the female silkworm pupae parasitized by E. sorbillans. In total, 50 differentially expressed proteins (DEPs) were successfully identified, of which 36 proteins w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Immune gene expression, melanization and apoptosis were activated in silkworm integumental epithelium post E. bombycis parasitization [14]. Proteomic analysis revealed that the levels of innate immune proteins and apoptosis-related proteins were induced in the hemolymph of E. sorbillans-parasitized silkworms at a late infection stage [15]. These findings demonstrated that different host tissues exhibit diverse responses to tachinid parasitoids.…”
Section: Introductionmentioning
confidence: 84%
“…Immune gene expression, melanization and apoptosis were activated in silkworm integumental epithelium post E. bombycis parasitization [14]. Proteomic analysis revealed that the levels of innate immune proteins and apoptosis-related proteins were induced in the hemolymph of E. sorbillans-parasitized silkworms at a late infection stage [15]. These findings demonstrated that different host tissues exhibit diverse responses to tachinid parasitoids.…”
Section: Introductionmentioning
confidence: 84%
“…One cellular immune reaction against invading parasitoid eggs and larvae is encapsulation with hemocytes followed by melanization ( Yamashita et al, 2019 ; Yang et al, 2021 ). Recent studies identified enhanced expression of innate immunity components of toll and melanization pathways, cytokines or proteolytic enzymes, and oxidative reactions in B. mori following Exorista sorbillans parasitoidism ( Pradeep et al, 2013 ; Anitha et al, 2014 ; Jayaram et al, 2014 ; Makwana et al, 2017 ; Pooja et al, 2017 ; Xu et al, 2019 ). We showed here that around 35% parasitized larvae have undergone successful larval–pupal transition and around 25% of the successful pupated parasitized hosts could eliminate tachinid larvae either in larval or pupal stage and undergo successful eclosion.…”
Section: Discussionmentioning
confidence: 99%
“…Since post-genomic approaches cannot be used for fluid tissues such as hemolymph, their analysis is restricted to proteomics. Indeed, several proteomics studies of fruit fly [19][20][21], silkworm [22,23], mosquitoes [24,25], and honeybee [26] hemolymph in different biological contexts (infection, nutrition, growth . .…”
Section: Introductionmentioning
confidence: 99%